Let me find a,b,h,k for you :)
y = –3(x + 7)^2 – 10
-> y = –3(x - (-7))^2 – 10 (Notice the negative!)
-3 would be a, the vertical stretch
1 would be b, since there's nothing in front of x
Vertex would be at (-7, -10)
Now let's take a look at our basic parabola, y = x^2
a = 1
b = 1
Vertex: (0,0)
Since our a constant is a negative number AND greater than 1, we can say that this function has been stretch vertically of factor 3.
Then b is the same.
Vertex (0,0) and (-7,-10)
We can say that the parabola is moved of 7 to the left and 10 downward.